ACE I/D polymorphism is a risk factor of Alzheimer's disease but not of vascular dementia - Kölsch, Heike; Jessen, F.; Freymann, N.; Kreis, Markus; Hentschel, Frank; Maier, W.; Heun, R. (Neuroscience letters, 2005)
Different studies have investigated the effect of the angiotensin converting enzyme (ACE) insertion/deletion (I/D) polymorphism on the risk of Alzheimer dementia (AD). However, results on the association of the ACE-I allele with AD have been inconclusive. A recent meta-analysis reported an association of the I-allele with the risk of AD. A few small studies also investigated the effect of ACE polymorphism on the risk of vascular dementia (VD). We have investigated the effect of ACE I/D polymorphism in 351 AD and 155 VD patients and 348 healthy controls. We found the I/I genotype to be associated with an increased risk of AD, but not with the risk of VD. Cell-specific effects of ACE polymorphism are suggested, additional studies on neuronal cells might help to understand the role of this polymorphism in AD.